2021
DOI: 10.51176/1997-9967-2021-2-164-177
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital technologies in the development of logistics in Kazakhstan in the formation of Industry 4.0

Abstract: The purpose of this research is to study the provision of logistics services in the context of Industry 4.0 and analyze the level of application of modern technologies in the field of transport and logistics based on an assessment of the relationship between technological readiness, the development of innovation and the efficiency of logistics in Kazakhstan. Based on data from the World Bank and the World Economic Forum on the Logistics Performance Index (LPI) and Global Competitiveness (GCI), a correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Currently, investing in OI equals higher productivity, even though it could occasionally come across difficulties from employees or customers, training outlays and, undeniably, a significant financial cost (Mihalič & Buhalis, 2013). Overall, previous studies revealed that technology readiness and innovativeness potential form the basis for exhibiting digital transformation (Moldabekova et al, 2021). In addition, Phuong et al (2015) suggested that cloud computing as an advanced technology innovation is positively affected by the technology readiness and innovativeness as organizational factors of the TOE framework within SMEs (Phuong et al, 2015).…”
Section: The Moderating Role Of Organizational Innovativenessmentioning
confidence: 99%
“…Currently, investing in OI equals higher productivity, even though it could occasionally come across difficulties from employees or customers, training outlays and, undeniably, a significant financial cost (Mihalič & Buhalis, 2013). Overall, previous studies revealed that technology readiness and innovativeness potential form the basis for exhibiting digital transformation (Moldabekova et al, 2021). In addition, Phuong et al (2015) suggested that cloud computing as an advanced technology innovation is positively affected by the technology readiness and innovativeness as organizational factors of the TOE framework within SMEs (Phuong et al, 2015).…”
Section: The Moderating Role Of Organizational Innovativenessmentioning
confidence: 99%
“…Seen from a macroeconomic perspective, where there is insufficient research in the existing literature, innovation and technological readiness can favourably influence the development of logistics (Moldabekova et al, 2021). Their research first provided evidence of the positive impact of innovation factors and modern technology on all elements of countries' logistics performance (measured using the LPI), thus establishing one of the ways to stimulate the development of Logistics 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a need to develop mutually beneficial mechanisms for the government and the private sector to implement digital technologies in the transport and logistics industry in the country. The introduction of electronic document management in freight and transport processes, transparency in supply chains, automation of loading and unloading operations in warehouses, transport and logistics centres and terminals, and other ways of digitalization are extremely important [6].…”
Section: Main Provisionsmentioning
confidence: 99%